Rendimiento académico y bienestar personal subjetivo de posgraduación stricto sensu - Vargas Maldonado, Thiago (2022)
The research analyzes the relationship between academic performance and subjective personal well-being of postgraduate students stricto sensu. Academic performance consubstantiated aspects that exceed exclusively quantitative metrics and are pointed out in the literature as important predictors for the academic development of the subject. The subjective personal well-being was represented from the dimensions: global satisfaction with life, positive emotions and negative emotions. Three models of Multiple Linear Regression were proposed, using a sample of 378 students, in order to consider the variations of positive and negative emotions over time that affect overall satisfaction with life. The results indicated satisfaction with infrastructure, life satisfaction, positive emotions, marital status and lack of scholarship availability as important predictors of academic performance. We conclude that considering psychological elements and the personal characteristics of the students are important to foster adequate levels of performance in the post-graduate course. Thus, it is pertinent that student support policies, address students’ subjective needs and expand financial support, since non-scholars tend to have less dedication to postgraduate studies and consequently lower academic performance.